Effects of Intralesional Doxycycline in the Treatment of Cystic Hygroma (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Cystic lymphangioma is a congenital lymphatic malformation.The present study was conducted to find out the effects of intralesional Doxycycline in the treatment of cystic hygroma.Materials and methods: This prospective study was conducted among 30 children with cystic hygroma in the Division of Pediatric Surgery, Dhaka Medical college Hospital, Dhaka, from July 2019 to June 2021. All patients were followed up for six months. In every follow up size of the lesion was determined and adverse effects were also noted.Results: More than half of the cystic hygroma (53.3%) were in neck while 5 (16.6%) in axilla. Before treatment, the median size of cystic hygroma was 12.00 cm2 which significantly decreased to 0.75cm2after treatment (p